ISLAMIC BUSINESS ETHICS AND INFORMAL ISLAMIC EDUCATION AMONG MUSLIM ENTREPRENEURS IN ILORIN EMIRATE - Rasheed Olalekan AZEEZ; Sa’ad Bello YUSUF (Fakultas Ekonomi Universitas Negeri Medan, 2026)
This study examines the intersection of Islamic business ethics and informal Islamic education within the entrepreneurial culture of Ilorin Emirate, a historically significant centre of Islamic scholarship and commerce. It aims to analyse how core Islamic ethical principles—particularly trustworthiness (amānah), truthfulness (ṣidq), and justice (‘adl)—are embodied in the business practices of Muslim entrepreneurs and how these practices function as mechanisms of informal Islamic education. Adopting a qualitative documentary research design, the study relies on secondary data drawn from classical Islamic texts, contemporary academic literature, and socio-historical documentation on Ilorin’s marketplace traditions. Qualitative content analysis reveals that ethical business conduct operates as a lived pedagogical process through role-modelling, apprenticeship, daily interactions, and communal accountability. These mechanisms enable the internalisation and transmission of Islamic moral values beyond formal educational institutions. The findings demonstrate that the marketplace functions as an informal educational environment that contributes to moral formation, community cohesion, and sustainable ethical behaviour. The study contributes to Islamic education studies by conceptualising entrepreneurship as an underexplored but significant site of informal Islamic learning, thereby expanding the scope of Islamic education beyond schools and madrasahs to include everyday economic life.